BLOCKCHAIN IN THE INTERNET OF THINGS : BIBLIOMETRIC ANALYSIS - Agni Isador Harsapranata; Omar Pahlevi (Sean Institute, 2023)
The development of the Internet of Things is so rapid that it can be seen by using it to help human life. It can be seen in various health, education, plantations, agriculture, fisheries and other fields. With the Internet of Things in most aspects of human life, reliable data integrity is required, thus encouraging technological verification to ensure data integrity. In this research, the author uses bibliometric analysis using Vosviewer and Biblioshiny to determine the picture of blockchain and Internet of Things research. The author uses 11,302 journal data from 2016 to 2023; it can be seen that the highest H index ranking is given by the IEEE Internet of Things Journal